A new coincident index of business cycles based on monthly and quarterly series - Mariano, Roberto S. (Institutional Knowledge at Singapore Management University, 2003)
Popular monthly coincident indices of business cycles, e.g. the composite index and the Stock-Watson coincident index, have two shortcomings. First, they ignore information contained in quarterly indicators such as real GDP. Second, they lack economic interpretation; hence the heights of peaks and the depths of troughs depend on the choice of an index. This paper extends the Stock-Watson coincident index by applying maximum likelihood factor analysis to a mixed-frequency series of quarterly real GDP and monthly coincident business cycle indicators. The resulting index is related to latent monthly real GDP. [PUBLICATION ABSTRACT]